Seru dan Edukatif: Kahoot Pendidikan Pancasila untuk Semua - Krisna Kumalasari; Sutrisna Wibawa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The increasingly rapid development of globalization has triggered the development of education in the field of increasingly advanced technology. In the field of educational activities there is an adaptation of learning activities to technological developments. Based on this, of course the role of learning media is also needed in the field of education. The aim of the research is to analyze the application of the Kahoot application in Pancasila education to create exciting and educative learning. The research method uses qualitative research with a literature review approach. The results of the implementation carried out at SD Negeri 1 Pengasih from 20 November 2023 to 1 December 2023 show that Kahoot can increase students' understanding and involvement in the values ​​of Pancasila. In conclusion, Kahoot media can be used to support exciting and educational learning activities that are implemented in Pancasila education learning. Learning carried out in the classroom can use ICT-based media such as Kahoot. This is because the use of Kahoot media is easy to access, so it will indirectly have an impact on increasing student motivation. Innovation in learning is certainly needed in learning activities to create good learning and is related to the role of increasingly sophisticated technology.